Customers Satisfaction of Port Services Hunimua Central Maluku - Tanasale, Charlene Cleopatra; Saputro, Soemino Eko; Solikin, Solikin; Saptana, Saptana; Febriyanti, Febriyanti; Maemunah, Siti (Institut Transportasi dan Logistik Trisakti, 2023)
The aim of the research is to identify the factors that influence the satisfaction level of the Hunimua (South Maluku, Indonesia) crossing port service users. The study analyzes service performance on the level of service user’s satisfaction and customers’ loyalty at Hunimua ferry port. The study wants to find out the safety and security procedure in crossing transportation. The government stipulates minimum service standards for crossing transportation through Ministerial Regulations. The method used was Quantitative approach with a total sample of 100 passenger population at Hunimua ferry port after calculated using Slovin formula. The research used Path Analysis method. The results of the study indicate that the service performance has a positive and significant effect on customers’ satisfaction and loyalty by maintaining the quality service performance to meet the customers’ satisfaction. Customers’ interests have positive and significant effect on customers’ satisfaction and loyalty. Quality influences customers’ satisfaction and loyalty that could be traced from employees’ time to respond to customers appropriately, a sense of security during contact with staff, patience, company attention and understand the customers’ need. The variable of customers’ satisfaction could mediate the service performance and customers’ interest in customers’ loyalty.